Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.3892/ijo.2011.991
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of insulin-like growth factor-binding protein 3 by 5-fluorouracil (5-FU) leads to the potent anti-proliferative effect of androgen deprivation therapy combined with 5-FU in human prostate cancer cell lines

Abstract: Abstract. In this study, we investigated the synergistic mechanism of anti-androgen and 5-fluorouracil (5-FU) combination therapy against castration-resistant prostate cancer (CRPC). Four prostate cancer cell lines, LNCaP, 22Rv1, DU145 and PC3, were examined for their growth dependency on androgens and the insulin-like growth factor 1 (IGF1). We assessed the expression changes of certain growth factor receptors and regulating proteins when treated with 5-FU, and found that 5-FU increased the expression of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Bicalutamide was found to inhibit androgen-independent prostate cancer cell growth appeared through AR-independent pathways [ 45 , 46 ]. One study showed that combination of bicalutamide with other therapeutic agents enhanced the CRPC growth inhibition via up-regulation of insulin-like growth factor-binding protein 3 (IGFBP3) [ 47 ]. Also, previous study indicated that MUC1-C subunit suppressed AR expression through a posttranscriptional mechanism and resisted to bicalutamide treatment in androgen-dependent prostate cancer cells, this implied that inhibition of AR expression by MUC1-C led to develop more aggressive androgen-independent phenotype in prostate cancer cells that was sensitive to MUC1-C inhibition [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bicalutamide was found to inhibit androgen-independent prostate cancer cell growth appeared through AR-independent pathways [ 45 , 46 ]. One study showed that combination of bicalutamide with other therapeutic agents enhanced the CRPC growth inhibition via up-regulation of insulin-like growth factor-binding protein 3 (IGFBP3) [ 47 ]. Also, previous study indicated that MUC1-C subunit suppressed AR expression through a posttranscriptional mechanism and resisted to bicalutamide treatment in androgen-dependent prostate cancer cells, this implied that inhibition of AR expression by MUC1-C led to develop more aggressive androgen-independent phenotype in prostate cancer cells that was sensitive to MUC1-C inhibition [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that, in breast cancer, trastuzumab regulates IGFBP-2 and -3 expression, which impacts IGF1R downstream signaling (35). Cytotoxic agents can also regulate IGFBP secretion: increased secretion of IGFBP-3 in prostate cancer cells treated with 5-fluorouracil plays an important role in its pro-apoptotic effect (36). Thus, due to the complexities of the IGF system and its regulation, further investigation will be required to identify a reliable marker of IGF1R-based resistance to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of the tumor suppressor p53 in response to chemotherapy or radiotherapy plays an important part in the cytotoxic effects of these therapies [ 67 ]. Since the discovery of IGFBP3 as a p53-inducible gene in 1995 [ 68 ], studies in many cancer cell lines have demonstrated an increase in the expression of IGFBP-3 in response to treatment by chemotherapeutic drugs [ 69 – 71 ]. Because exogenous IGFBP-3 has proapoptotic activity in many cell types, including breast cancer cells, either when used alone [ 72 ] or in combination with other apoptotic agents such as C 2 ceramide [ 73 ], chemotherapy drugs [ 70 ], or radiation [ 19 ], the induction of IGFBP-3 in response to DNA-damaging therapies has been assumed to contribute to the cytotoxicity of these treatments.…”
Section: Igfbp-3 and The Dna Damage Response: Can Igfbp-3 Alter Rementioning
confidence: 99%